Effect of acute exercise in intraocular pressure: a meta-analysis - Alemán, Carolina (2019)
High intraocular pressure (IOP) affects visual health, since it is the main risk factor for glaucoma. The objective of this study was to know the effects of intense exercise on IOP. The methodology was based on meta-analyzed experimental studies that evaluated the effect of intense physical activity on IOP. The research of data included eight multidisciplinary databases. A PRISMA protocol was applied, with criteria of eligibility, methodological quality, and extraction of information by two researchers to guarantee reproducibility. The meta-analysis was based on random effects, heterogeneity with DerSimonian-Laird. As a result, twenty-nine articles were analyzed to obtain the effect size (ES): experimental groups included 1,016 subjects and control groups included 120 subjects. A total of 102 delta ES were calculated. The results of this study show an ES of 0.31 (IC 95% = from -0.46 to 1.08, Q = 16.15, I2 = 81.42 p ≤ 0.05) for the control group and an ES of -0.68 (IC 95% = from -0.95 to -0.41, Q = 1573.49, I2 = 99.80, p ≤ 0.05) for experimental groups. ES for aerobic exercise was -1.74 (IC 95% = from -2.11 to -1.36, Q = 723.48, I2 = 99.66, p ≤ 0.05), which shows a large effect, indicating a reduction of IOP. This result indicates a preventive strategy that should be taken into consideration. In regards to strength exercise, ES was 0.13, which indicates that there is no effect. In conclusion, IOP is reduced with intense aerobic exercise.